Eco-Friendly Nano-Additives: Energy, Exergy, and Environmental Impacts in Motor Vehicle Emission Control - Özer, Salih; Arslan, Ahmet; Doǧan, Battal; Tunçer, Erdal; Arslan, Omer (Society of Automotive Engineers Turkey, 2025)
This study investigates the performance and emission behavior of borax decahydrate nanoparticles when blended with biodiesel and commercial diesel fuels in diesel engines. Experimental tests were conducted at five different engine power levels: 1 kW, 2 kW, 3 kW, 4 kW, and 5 kW-to evaluate the impacts of these fuel blends on engine performance, emissions, energy efficiency, exergy, and exergoenvironmental parameters. The data collected demonstrated a general trend where higher engine power output led to increased heat generation. Among the tested blends, the D40W50P1 fuel achieved efficiencies of 15.236%, 15.466%, 18.290%, 25.606%, and 24.258% at the respective power levels, highlighting the positive effect of borax nanoparticle addition on engine performance. The inclusion of borax nanoparticles particularly improved the performance of diesel/waste cooking oil blends. The results also revealed that the D50W50 fuel blend performed optimally at 2 kW, whereas the D40W50P3 blend showed a notable improvement, achieving an efficiency increase of 12.10%. Furthermore, sustainability index values were consistently above 1, indicating a favorable environmental and energetic balance for all tested fuel blends. The lowest recorded sustainability index was 1.123, observed for the D50W50 blend. In terms of exergoenvironmental analysis, the D40W50P2 fuel blend demonstrated carbon dioxide (CO2) emissions of 311.69 kg/month at 1 kW and 786.34 kg/month at 5 kW. These results highlight the potential of borax nanoparticle additives to not only improve fuel efficiency and engine performance but also contribute to reducing environmental emissions. The results indicate that boron additives can enhance engine performance and energy efficiency while reducing CO2 emissions. Additionally, the improvement in the sustainability index reveals the potential of boron-based fuels from both environmental and economic perspectives. These findings serve as an important reference for future research and industrial applications related to alternative fuel additives. © 2025 Elsevier B.V., All rights reserved.
Keywords: Borax Decahydrate; Energy; Environmental; Exergy; Waste Frying Oil